The police identity crisis: hero, warrior, guardian, algorithm - Hunt, Luke William (Innovations in policing, 2021)
"This work provides a comprehensive examination of the police role from within a broader philosophical context. Contending that the police are in the midst of an identity crisis that exacerbates unjustified law enforcement tactics, the author examines various major conceptions of the police--those seeing them as heroes, warriors, and guardians. This book looks at the police role considering the overarching societal goal of justice and seeks to present a synthetic theory that draws upon history, society, psychology, and philosophy. Each major conception of the police role is examined in light of how it affects the pursuit of justice, and how it may be contrary to seeking justice holistically and collectively. The book sets forth a conception of the police role that is consistent with the basic values of a constitutional democracy in the liberal tradition. The author's intent is that clarifying the police role will likewise elucidate any constraints upon policing strategies, including algorithmic strategies such as predictive policing. This book is essential reading for thoughtful policing and legal scholars as well as those interested in political philosophy, political theory, psychology, and related areas. Now more than ever, the nature of the police role is a philosophical topic that is relevant not just to police officials and social scientists, but to everyone"--